Taxonomy of the South American genus Phyllopetalia (Odonata: Austropetaliidae) - Von Ellenrieder, Natalia (2005)
This synopsis of adult Phyllopetalia includes the synonymy of four genera (Phyllopetalia senior subjective synonym of Rheopetalia, Odontopetalia, Eurypetalia and Ophiopetalia), four species and one subspecies (P. apicalis senior subjective synonym of Rheopetalia rex and R. apicalis decorata, and P. pudu senior subjective synonym of Ophiopetalia araucana, O. auregaster and O. Diana). P. excrescens and P. altarensis are redescribed, and a neotype is designated for the latter. Keys to adults, illustrations of all diagnostic characters, and distribution maps of all species are provided.